A Semi-automatic Diagnosis of Hip Dysplasia on X-Ray Films - Yang, Guangyao; Jiang, Yaoxian; Liu, Tong; Zhao, Xudong; Chang, Xiaodan; Qiu, Zhaowen (Frontiers in Molecular Biosciences, 2020)
Background: Diagnosis of hip joint plays an important role in early screening of hip diseases such as coxarthritis, heterotopic ossification, osteonecrosis of the femoral head, etc. Early detection of hip dysplasia on X-ray films may probably conduce to early treatment of patients, which can help to cure patients or relieve their pain as much as possible. There is no method or tool for automatic diagnosis of hip dysplasia now. Results: A semi-automatic method for diagnosis of hip dysplasia is proposed. The contour of acetabulum, femoral head and the upper side of thigh-bone are manually marked. Feature points are extracted according to marked contours. Angles including CE, sharp and Tonnis angle which are commonly measured in clinical diagnosis, are automatically obtained. Samples, each of which consists of these three angle values, are used for clustering according to their densities in a descending order. Thus, a model for diagnosis of hip dysplasia is built. Experiments on 143 X-ray films including 286 samples (i.e., 143 left and 143 right hip joints) demonstrate the effectiveness of our method. According to the method, a computer-aided diagnosis tool is developed for the convenience of clinicians. Conclusions: This data-driven method provides a more objective measurement of the angles. Besides, it provides a new criterion for diagnosis of hip dysplasia other than doctors’ experience deriving from knowledge-driven clinical manual, which actually corresponds to very different way for clinical diagnosis of hip dysplasia.